Development of Analytical Thinking Ability on Mathematics by using Learning and Enjoying Model with Mind Mapping for Pre-Service Teacher in Mathematics Program (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this research were to study analytical thinking ability on mathematics, to compare analytical thinkingability on mathematics with the criteria, and to study collaboration, teamwork and leadership after using Learning and EnjoyingModel with Mind Mapping. The samples were pre-service teachers in Mathematics program. The instrument consists of theprocess of Learning and Enjoying Model with Mind Mapping, the test about analytical thinking ability on mathematics, and thecollaboration, teamwork and leadership questionnaire. Data analyzed by percentage, mean, standard deviation, and t-test onegroup. The results found that, pre-service teachers had 74.64 percent of analytical thinking ability on mathematics and it washigher than the criteria of 70 percent at .05 level of significance, when considered in each aspect found that the analysis ofelement had highest percent, then the analysis of relationship, and analysis of organizational principles respectively. Moreover,pre-service teachers had collaboration, teamwork and leadership as a whole at a high level. Considering that everyone willing toaccept the results of their work in highest average, followed by every member is important for work success according to goal,they believe that every members of the group can work towards their goals, and all members are involved in decision-makingrespectively. Pre-service teachers commented, this learning process has easy steps to implement with students. Creating a MindMapping is connecting a content to help understand the details and whole of the contents